(untitled) (Research, Society and Development, 2022)
Cassava is one of the agricultural activities of great importance throughout the country, being one of the most socioeconomically expressive crops in Brazil, with the state of Pará being the largest national producer. Based on this information, the objective of this study was to characterize the technological level of cassava, identify the forms of use and by-products of cassava in the Soledade community, municipality of Moju-Pará. Data collection was carried out through the application of questionnaires to small farmers, over 18 years of age of both sexes. The study found that 83% of the interviewed producers do not carry out soil analysis on their properties. On the reasons for not carrying out the soil analysis, 53.33% of the interviewees justify that the land in the region is productive. Regarding the use of fertilizers, it was found that 100% of respondents do not use fertilizer in the production of cassava, where 53.33% confirm that the soil is productive and 13.33% find fertilization expensive. With regard to by-products extracted from cassava, it was found that 23.33% of respondents produce (flour, tapioca, tucupi and gum). Regarding the form of disposal, 43.33% reported discarding in the ecosystem. Regarding the cassava handling process, it was identified that a large amount of waste is produced, where 43.34% is discarded by producers. Regarding the disposal of waste from cassava production, 83.33% of the interviewed producers said they did not have difficulties in disposing of waste from cassava, however, if discarded incorrectly, they can become an aggravating factor for the environment. In view of the results, it is concluded that: cassava cultivation in the Soledade community is characterized by a low technological level; it has diversified ways of using cassava, highlighting the roasting of flour; the residues are mainly used as fertilizer. In this sense, it is expected that they serve as a tool to assist in decision making that provide improvements in the cultivation techniques used and greater use of cassava residues.